IMPLEMENTASI PERATURAN MAHKAMAH AGUNG TENTANG E-COURT UNTUK MEWUJUDKAN ASAS SEDERHANA, CEPAT DAN BIAYA RINGAN DI PENGADILAN AGAMA PAMEKASAN - Erie Hariyanto; Sundusiyah Sundusiyah (Arena Hukum, 2022)
This article analyzes the implementation of the Indonesian Supreme Court Regulation Number 1 of 2019 concerning E-Court in order to realize the simple, fast and lowcost principles at the Pamekasan Religious Court. This research uses qualitative descriptive analysis method combined with socio-legal approach. The results of the study found that the principle of simple, fast and low cost in the settlement of family law cases included: (a) Facilitating the registration process and down payment due to online (e-Filling) and (e-payment) based so that registration and payments are made without queuing (b) case files are properly archived and accessible from anywhere and anytime (c) summons and hearings that can be carried out relatively quickly do not need to wait a week and on the basis of the agreement of the attorney. Factors supporting the implementation of E-Court save time and costs in the case registration process and subsequent processes, the trial delay period can be faster than the manual one so as to allow the settlement of family law cases according to fast judicial principles, documents are archived properly and can be accessed without limited space and time.